Wawasan Hadis Tentang Hubungan Mahram Karena Penyusuan - Suarning Suarning; Abdul Jalil; Muliati Muliati (LPPM IAIN Parepare, 2020)
The aims of this study was to conduct a hadist insight into the relationship of mahram due to breastfeeding. The method used was the thematic method with a historical approach. Other approaches was used such as pedagogical, sociological, linguistic and normative theological in understanding hadist. The analysis technique was used textual, contextual, and intertextual analysis. The Insight of the Prophet's hadist about sibling’s mahram shows the existence of breastfeeding provides the absolute prohibition of marriages from and above associated with breastfeeding. All children who were breastfeeding directly and sprayed ware classified as children of sesusuan causing a mahram relationship. The process of giving breastfeedingto the baby, then contextually breast milk that has been pleasurable the baby can result in the legal status of mahram. For this reason, a woman when she wants to make a decision for breastfeeding children should be careful with regard to the frequency of breast milk, quality or content of breast milk, as well as the time or age of breast milk.